Penerapan Metode Role Play dalam Pembelajaran Bahasa Inggris pada Siswa di LPK Mahima Institut Indonesia - Dewi, I Gede Ayu Wisma; Sukraningsih, I Gusti Ayu Gede (Wacana : Majalah Ilmiah Tentang Bahasa, Sastra Dan Pembelajarannya, 2023)
This research focuses on the application of the role-play method to students' English speaking skills at the Mahima Institute of Indonesia (LPK) Course and Training Institute. The role-play method is also called role-playing. Role play is a form of learning method, where students are actively involved in playing a role. Through fun playing activities, children try to investigate and gain experience from themselves, other people, and the environment around them. Students at LPK Mahima Institute Indonesia use several learning media, one of which is presentation media. Presentation is a potent combination of design, implementation, the message contained, and the intention to catch the viewer's attention. Speaking is a productive language skill that is used orally to express thoughts and feelings so that by using the role-play method students can be actively involved in learning to speak English which can motivate students.